ISLAMIC EDUCATIONAL POLICIES IN THE PHILIPPINES: ITS EVOLUTION AND CURRENT PROBLEMS - Zainal Dimaukom Kulidtod (Faculty of Education Universitas Negeri Malang, 2018)
Islamic education aims to develop both the intellectual as well as the spiritual aspects of man. However, despite the considerable number of Bangsamoro (i.e., Muslim Filipinos) in this country, said the system is not observed in the Philippines since this is a secular nation whose educational system is copied from the West. Being patterned from the European style, our public-school system gives emphasis only on the human knowledge, while the Islamic (i.e., Madrasah) learning system concentrates on the divine aspect. Since these two systems of knowledge are taught separately, the present educational system in the country is not much effective in meeting the needs of the Muslims.In addressing this educational challenge, the Philippine government has initiated various programs and policies sanctioned by the following laws, such as: (i) the Letter of Instruction No. 1221 of 31 March 1982; (ii) the Letter of Instruction No. 17-A, (iii) the Muslim Mindanao Autonomy Act No. 14, (iv) the DepED Order No. 51 of 28 August 2004, (v) the DepED Order No. 40 of 19 May 2011, and (vi) the different provisions of the Peace Agreements between the Bangsamororebels and the Philippine government.However, despite these legal issuances and programs, still the Islamic education of the Muslims in the Philippines has been hampered by financial, administrative and structural problems. Keywords: islamic education, secular education, balanced education, madrasah/madaaris, bangsamoro/moro people